Efeito do extrato de folhas de mamona (Ricinus communis) sobre a cigarrinha do milho Dalbulus maidis (Delong & Wolcott) - Besson, Gabriel Antonio (2021)
Corn (Zea mays L.) has a high productivity potential, however this crop is attacked by a complex of pests which can compromise this productivity. In this context, corn leafhopper (Dalbulus maidis DeLong & Wolcott) is a pest that causes both direct and indirect damage for this crop. For the management of this pest, the application of synthetic insecticides is the main method, however, in order to obtain other alternative control methods that cause less environmental impact, the use of plants with insecticidal activities, such as castor bean (Ricinus communis L.), has been encouraged. Therefore, the objective of this work was to evaluate the effect of castor leaves extracts (ricinin) for controllling D. maidis on corn crops. For this, an experiment in field condition was carried out in randomized block design with 3 replications, to be tested 4 treatments: two treatments of castor extract with concentrations of 10 ppm of ricinine and 100 ppm of ricinine, a positive control based on commercial insecticide Imidacloprid and a negative control based on water. After the corn cultivation reached the VT stage, for a period of 23 days, 14 evaluations were performed by directly counting the number of D. maidis in 5 plants in the central line of each experimental plot. Over this period, there were three treatments applications, on the dates of the 3rd, 5th and 12th evaluations. Significant differences were detected in the mean density of D. maidis per plant among treatments. The castor extracts treatments and the insecticide Imidacloprid obtained similar mean density per plant. It was also observed that not only for the same date (pre and post treatments application) but also over the time, that the treatments with castor extracts and the commercial insecticide reduced the population of D. maidis. According to the results found in the present study, the extract of R. communis has an effect on the corn leafhopper (D. maidis), and therefore, could be considered for the control of this pest.